Energy Optimization of Dimethyl Ether (DME) Production Process from Methanol Dehydration - Ghoffaru, Al Fath; Grasia, Jovian Luxioctafiano; Wijaya, Athallah Akmal; Ramadhan, Narendra Dzaki; Saputro, Andre Nur; Maharani, Anggistia (UPT Laboratorium Terpadu, Universitas Diponegoro, 2024)
The increasing demand for sustainable and clean alternative fuels has driven the focus on dimethyl ether (DME), an environmentally friendly and non-toxic chemical with high potential as a fuel and industrial solvent. DME can be produced from various raw materials such as natural gas, methanol, biomass, and coal. This study investigates the optimization of DME production from methanol dehydration using a fixed-bed plug flow reactor and γ-Al₂O₃ catalyst, emphasizing energy efficiency improvements. Modifications were implemented in the Aspen HYSYS simulation by replacing the conventional heater with heat exchanger and utilizing heat generated during cooling process for another heating process. The results demonstrated a significant reduction 65.8 % in net energy consumption from 8.54×106 kJ/h to 2.92×106 kJ/h, validating the effectiveness of these modifications by leveraging Aspen HYSYS simulations, the proposed design achieved high process efficiency while maintaining the target DME purity of 99.95 % produced. This research highlights the potential of heat integration strategies to enhance the economic and environmental performance of DME production processes. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).